2014
DOI: 10.1534/genetics.113.160531
|View full text |Cite
|
Sign up to set email alerts
|

Gene Duplication, Lineage-Specific Expansion, and Subfunctionalization in the MADF-BESS Family Patterns theDrosophilaWing Hinge

Abstract: Gene duplication, expansion, and subsequent diversification are features of the evolutionary process. Duplicated genes can be lost, modified, or altered to generate novel functions over evolutionary timescales. These features make gene duplication a powerful engine of evolutionary change. In this study, we explore these features in the MADF-BESS family of transcriptional regulators. In Drosophila melanogaster, the family contains 16 similar members, each containing an N-terminal, DNA-binding MADF domain and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 69 publications
0
37
0
1
Order By: Relevance
“…Recent gene-specific and genome-wide studies, however, produced evidence for a role of genetic redundancy in securing developmental, genetic, and environmental robustness over hundreds of millions of years in part through conservation of genetically redundant gene paralogs (Celniker et al, 2002;Maslov et al, 2004;Pasek et al, 2006;Dean et al, 2008;Vavouri et al, 2008;Yang et al, 2009;Bao et al, 2012;Buscà et al, 2015). As an example, the recent discovery of partially, yet longterm conserved redundant roles of paralogs of the Drosophila lineage expanded MADF-BESS transcription factor family in the development of the wing hinge has been proposed to be explained by the benefit of developmental robustness (Shukla et al, 2014).…”
Section: Increased Developmental Genetic Redundancy In the Brachyceramentioning
confidence: 99%
“…Recent gene-specific and genome-wide studies, however, produced evidence for a role of genetic redundancy in securing developmental, genetic, and environmental robustness over hundreds of millions of years in part through conservation of genetically redundant gene paralogs (Celniker et al, 2002;Maslov et al, 2004;Pasek et al, 2006;Dean et al, 2008;Vavouri et al, 2008;Yang et al, 2009;Bao et al, 2012;Buscà et al, 2015). As an example, the recent discovery of partially, yet longterm conserved redundant roles of paralogs of the Drosophila lineage expanded MADF-BESS transcription factor family in the development of the wing hinge has been proposed to be explained by the benefit of developmental robustness (Shukla et al, 2014).…”
Section: Increased Developmental Genetic Redundancy In the Brachyceramentioning
confidence: 99%
“…Among all known proteins (not just the ones in our data set) with an inferred BESS domain (InterPro identifier IPR004210), more than 80% are restricted to insects and more than 50% are restricted to diptera. A comparison among drosophilids has shown that the BESS domain family expanded through duplications in a lineage-specific way approximately 40 million years ago (Shukla et al 2014). In our dataset, five of 107 proteins have a BESS domain (SU(VAR)3-7, LHR, BEAF-32, CC20, and CC25).…”
Section: Recent Green Proteins Associate With the Expansion Of The Bementioning
confidence: 84%
“…The MADF domain is similar to the SANT domain (a domain found in Dom, as well as ISWI and BRM), and was first identified in the transcriptional activator, Adh transcription factor 1 (Adf-1). Proteins with the MADF domain have been found to act as both activators and repressors [ 35 ]. It may be relevant that 4 of the 5 proteins in our study that contain a MADF domain behaved similarly in the assay for dom modification ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%